Molecular Modeling of Microporous Structures of Carbide-Derived Carbon-Based Supercapacitors - Schweizer, Sabine; Meißner, Robert; Amkreutz, Marc; Thiel, Karsten; Schiffels, Peter; Landwehr, Johannes; Etzold, Bastian J.M.; Hill, Jörg Rüdiger (Journal of Physical Chemistry C, 2017)
Microporous carbide-derived carbons are an important structural class for various technological applications. We present two possible strategies based on molecular dynamics simulations for modeling microporous amorphous carbon. In addition, we have investigated the influence of the precursor structure and simulation parameters on the porosity of the final model structure. We observed a minor influence of the precursor structure on the porosity and found that the structural properties such as pore size and hybridization in the modeled carbon structures agree well with experimental findings. Moreover, CO2 adsorption isotherms have been simulated using Monte Carlo simulations for comparsion with experimental data. In this context, we have also considered partially oxidized carbon structures for which an increased uptake of CO2 was observed. (Chemical Equation Presented).
CRIS-Team Scopus Importer:2023-08-15